2021
DOI: 10.3748/wjg.v27.i24.3668
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of the brain-gut interaction and eating disorders

Abstract: BACKGROUND Eating disorders (ED) involve both the nervous system and the gastrointestinal tract. A similar double involvement is also found in disorders of the brain-gut interaction (DGBI) and symptoms are sometimes similar. AIM To find out where there is an association and a cause-effect relationship, we looked for the comorbidity of DGBI and ED. METHODS A systematic review was undertaken. A literature search was performed. Inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
0
9
0
5
Order By: Relevance
“…In der International Classification of Diseases and Related Health Problems der World Health Organization (WHO) ICD-11 werden als wichtigste Störungen zusätzlich die etwas seltenere Pica und die Rumination erwähnt [10]. Pica zeichnet sich aus durch Verzehren von Non-food-Gegenständen (Papier oder andere Objekte), die Rumination durch wiederholtes Hervorwürgen von Nahrung über einen Monat hinweg, wobei keine andere Erkrankung zugrunde liegen darf, welche das Verhalten besser erklärt [12,13].…”
Section: Tabelleunclassified
“…In der International Classification of Diseases and Related Health Problems der World Health Organization (WHO) ICD-11 werden als wichtigste Störungen zusätzlich die etwas seltenere Pica und die Rumination erwähnt [10]. Pica zeichnet sich aus durch Verzehren von Non-food-Gegenständen (Papier oder andere Objekte), die Rumination durch wiederholtes Hervorwürgen von Nahrung über einen Monat hinweg, wobei keine andere Erkrankung zugrunde liegen darf, welche das Verhalten besser erklärt [12,13].…”
Section: Tabelleunclassified
“…Whether the gastric dysmotility is secondary to food restriction, emesis, or is also influenced by patient nutritional state, and is not a primary disorder, is unclear. 76 In 2013, the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) included a new condition called avoidant/restrictive food intake disorder (ARFID), in which patients want to prevent feared negative consequences (e.g., vomiting), have low interest in eating, low appetite, or aversion to sensory characteristics of food, resulting in nutritional deficiencies. 77,78 Recently, it was shown that more than 50% of patients with gastroparesis/dyspepsia symptoms have significant symptoms of feeding and eating disorders, and almost 40% met the criteria for ARFID.…”
Section: Evidence Literature Reviewmentioning
confidence: 99%
“…A systematic review evaluating the association between ED and disorders of gut‐brain interaction showed that anorexia nervosa and bulimia nervosa were the most frequent ED associated with gastroparesis. Whether the gastric dysmotility is secondary to food restriction, emesis, or is also influenced by patient nutritional state, and is not a primary disorder, is unclear 76 . In 2013, the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) included a new condition called avoidant/restrictive food intake disorder (ARFID), in which patients want to prevent feared negative consequences (e.g., vomiting), have low interest in eating, low appetite, or aversion to sensory characteristics of food, resulting in nutritional deficiencies 77,78 .…”
Section: Ten Controversies In Gastroparesismentioning
confidence: 99%
“…Diabetic gastroparesis (DGp) is a gut motility disorder associated with abnormal gastric emptying (GE) when there is no mechanical obstruction along the gastrointestinal (GI) tract [ 1 , 2 ]. DGp is characterized by severe nausea, vomiting, bloating, early satiety, abdominal pains, nutritional deficiencies, and poor glycemic control [ 3 ].…”
Section: Introductionmentioning
confidence: 99%